Takhrij and Syarah Agrotechnology Hadith: Cultivation advice - Hanif Taruna Pratama; Wahyudin Darmalaksana; Liberty Chaidir (UIN Sunan Gunung Djati Bandung, 2021)
The purpose of this research is to discuss the hadith of the Prophet about the recommendation of farming. This research method is qualitative through the takhrij and sharah hadith approaches with agrotechnological analysis. The results and discussion of this research is that farming is a narrow definition of agriculture. Agriculture is an activity of utilizing biological resources carried out by humans to produce food, industrial raw materials, or energy sources as well as to manage the environment. The conclusion of this research is takhrij and syarah hadith of the Prophet about the suggestion of farming according to the hadith of the prophet SAW